Screening antibiofilm activity of invasive plants growing at the Slope Merapi Mountain, Central Java, against Candida albicans - Sufi Desrini; Marion Girardot; Christine Imbert; Mustofa Mustofa; Titik Nuryastuti (BMC, 2023)
Abstract Background Candida albicans causes high-mortality candidiasis. Antifungal drug resistance demands the development of virulence factor-targeting drugs, particularly antibiofilm. This study screened the effects of five invasive plants growing in Indonesia (Mimosa pudica, Lantana camara, Acacia mangium, Ageratina riparia, and Mikania micrantha) against C. albicans biofilms. Antifungal activity, antiphospholipase activity, biofilm morphology of C. albicans, and cytotoxic capacity were also evaluated. Methods Maceration was used to extract the plants, and the most active extract inhibiting the biofilms was fractionated using liquid-liquid fractionation. Antibiofilm activity was determined by a colorimetric assay, MTT. Antifungal activity was tested using the broth microdilution method. A phospholipase assay was performed using the egg-yolk agar method. Influence on the C. albicans morphology was assessed using scanning electron microscopy (SEM). The cytotoxic effect was carried out against Vero and HeLa cell lines. Results M. pudica extracts showed the most potent antifungal efficacy with minimum inhibitory concentration (MIC) of 15.62 µg/mL and 7.81 µg/mL for aerial parts and roots, respectively. At high concentrations (500 µg/mL and 250 µg/mL), ethanol extract of M. pudica aerial parts strongly inhibited the phospholipase activity. Ethyl-acetate fraction of M. pudica aerial parts demonstrated the most potent antibiofilm activity against 24 h old biofilm of C. albicans with an inhibitory concentration (53.89%) of 62.5 µg/mL showed no cytotoxicity in both Vero and HeLa cells. This fraction affected the morphology of C. albicans and contained promising compounds for inhibiting the 24 h old biofilm of C. albicans. Conclusions Invasive M. pudica plant inhibited the growth of planktonic C. albicans cells and its ethyl acetate fraction decreased the metabolic activity of C. albicans biofilms. This result demonstrates the potential of invasive M. pudica plant to reduce biofilm-associated candida infection.